2015
DOI: 10.1021/acs.orglett.5b02302
|View full text |Cite
|
Sign up to set email alerts
|

Carbonylative Mizoroki–Heck Reaction of Alkyl Iodides with Arylalkenes Using a Pd/Photoirradiation System

Abstract: A carbonylative Mizoroki-Heck reaction using alkyl iodides was achieved with a Pd/photoirradiation system using DBU as a base. In this reaction, alkyl radicals were formed from alkyl iodides via single-electron transfer (SET) and then underwent a sequential addition to CO and alkenes to give β-keto radicals. It is proposed that DBU would abstract a proton α to carbonyl to form radical anions, giving α,β-unsaturated ketones via SET.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
19
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(20 citation statements)
references
References 41 publications
0
19
0
1
Order By: Relevance
“…2 In prior studies, we developed a carbonylative variant of this reaction that yields cyclic enones from alkyl iodides and pendant alkenes (Figure 1). 3 We became interested in pursuing an alternative process involving alkene difunctionalization (carboacylation). 4 Prior to our studies there was limited precedent for this class of alkene difunctionalization; a photochemical palladium-catalyzed carboacylation has been reported, but requires excess alkyl iodide (1.5 equiv) and was limited to ketone synthesis using alkyl-boranes.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…2 In prior studies, we developed a carbonylative variant of this reaction that yields cyclic enones from alkyl iodides and pendant alkenes (Figure 1). 3 We became interested in pursuing an alternative process involving alkene difunctionalization (carboacylation). 4 Prior to our studies there was limited precedent for this class of alkene difunctionalization; a photochemical palladium-catalyzed carboacylation has been reported, but requires excess alkyl iodide (1.5 equiv) and was limited to ketone synthesis using alkyl-boranes.…”
mentioning
confidence: 99%
“…Bromopentacarbonylmanganese(I) and cobalt(0) carbonyl were both ineffective as catalysts (entries 2–3), as was Pd(PPh 3 ) 4 , which we have previously used in a number of catalytic C–C bond-forming reactions involving alkyl iodides (entry 4). 2e,3a,9 Amine bases could be used in the reaction, although yields were slightly diminished (entry 5). Reactions performed at various levels of CO pressure indicated that while reactions using a balloon of CO (1 atm) were unsuccessful, high pressures were not required (entries 6–7).…”
mentioning
confidence: 99%
“…Alkenyl-carbonyl disconnection for the synthesis of α, -unsaturated carbonyl compounds. [278] Another example of photocatalytic, acyl radical alkenylation was recently reported recently by Zhu et al [279] The authors used C2-acyl-substituted benzothiazolines as acyl radical precursors and 1,1-dicyano-1-alkenes, in the presence of hypervalent iodine reagents to obtain , -dicyanoenones in 50-80 % yield. Additionally, few examples involving acylation of alkynes, followed by subsequent cyclization, were reported.…”
Section: Generation Of Alkenyl Carbonylsmentioning
confidence: 98%
“…Arylketonen ( 89 ; Weg b) . Mit demselben Pd/Bestrahlungs‐System wurde kürzlich eine carbonylierende Mizoroki‐Heck‐Kupplung zur Herstellung α,β‐ungesättigter Ketone 90 entwickelt (Weg c) . Das Keton 88 ist auch aus Cyclohexancarbonsäure über eine photoredoxkatalytische decarboxylierende/carbonylierende Alkinylierung erhältlich …”
Section: Eine Fallstudie: Photoinduzierte Carbonylierungenunclassified